Determination of pedagogical principles for building functional science literacy of school children - Dwysengalievna, Maimatayeva Assiya; Danakul, Kazakhbayeva; Sholpan, Karbayeva; Kalampyr, Zhumagulova; Zhazira, Bitibayeva; Setiawan, Edi (Institute of Advanced Engineering and Science, 2025)
In this study, it was aimed to determine the pedagogical principles for building functional science literacy of school children in line with the Program for International Student Assessment (PISA) by examining the performing countries in PISA. The statistical results of the PISA results reports of China, Singapore, Hong Kong and Estonia were compared with the results of Kazakhstan. It was concluded that students in the top-ranked countries actively participate in scientific activities, enjoy practicing scientific activities, exhibit high-level cognitive skills, test and monitor the results of scientific research, and compete in national and international activities. The economic status of the family, learning environment, discipline, school equipment, and the number of teachers in the school are among the factors affecting children’s science literacy. Teachers’ continuous participation in in-service trainings, keeping their motivation at a high level, choosing different teaching methods, encouraging students to conduct research and activating high-level cognitive skills were considered among the most important reasons for good results in science PISA research. It is recommended that countries that want to rank higher in an international platform such as PISA should implement student-centered activities in their educational reforms and create educational environments where students can test their high-level skills.